Prospective Surveillance for Breast Cancer–Related Arm Lymphedema: A Systematic Review and Meta-Analysis. Issue 9 (20th March 2022) - Rafn, Bolette S.; Christensen, Jan; Larsen, Anders; Bloomquist, Kira
Abstract : PURPOSE: The call to integrate prospective surveillance for lymphedema into cancer care pathways is building momentum to enable early intervention and prevent the progression of the condition. We offer a critical evaluation of the literature on prospective surveillance and early management for cancer-related lymphedema and evaluate the effect of such programs in preventing chronic lymphedema (CRD42019137965). METHODS: Five databases and two registries were searched for randomized controlled trials or observational studies that assessed the incidence or prevalence of lymphedema associated with participation in a prospective surveillance program, published until February 26, 2021. Numbers triggered for early lymphedema management, resolved, and chronic lymphedema were extracted. Pooled relative risk (trials) and pooled rate (cumulative incidence; observational studies) of chronic lymphedema was calculated. Subgroup analyses assessed the effect of study design, length of follow-up, and extent of axillary surgery. RESULTS: Twenty-three studies were included, of which 21 studies evaluated breast cancer–related arm lymphedema (BCRaL). Participation in prospective surveillance with early management reduced the risk of chronic BCRaL versus usual care (relative risk 0.31; 95% CI, 0.10 to 0.95; two randomized controlled trials; N = 106). The pooled rate of chronic BCRaL was 4% (95% CI, 3 to 6; 15 observational studies; N = 3, 545), and 6% (95% CI, 4 to 9) when restricted to participants with axillary lymph node dissection (12 studies; N = 1, 527). CONCLUSION: The findings suggest that participation in prospective surveillance with early management reduces the risk of chronic BCRaL. Only a minority of patients at high risk of lymphedema because of axillary surgery developed chronic lymphedema. More robust research is needed to determine whether prospective surveillance with early management can reduce the risk of chronic lymphedema, particularly among cancer survivors other than breast cancer.